Radon transport events associated with the impact of a NORM repository in the SW of Europe. (15th November 2021) - Gutiérrez-Álvarez, I.; Guerrero, J.L.; Martín, J.E.; Adame, J.A.; Vargas, A.; Bolívar, J.P.
Abstract: Two radon measurement stations located to the north and south of a NORM (Naturally Occurring Radioactive Materials) repository of phosphogypsum (southwest of Europe) were used to monitor radon behavior during 2018. The stations are located at opposing sides of the repository, one in Huelva City to the north and other one in a rural area to the south. This setup aimed to identify the influence of the NORM repository on each station and use radon levels as a marker of atmospheric transport in the local area. To achieve this, a comparison was carried out with other coastal stations in the south of Spain, finding higher average concentrations in Huelva City, 3.3 Bq m −3 . Hierarchical clustering was applied to identify days with different radon patterns at each Huelva station, detecting possible local radon transport events from the repository. Three events were investigated with WRF (Weather Research and Forecasting) and FLEXPART-WRF (FLEXible PARTicle dispersion model). It was found that both sampling sites required atmospheric stagnant conditions to reach high radon concentration. However, under these conditions the urban station showed high radon regardless of wind direction while the rural station also required radon transport from the repository, either directly or indirectly. Graphical abstract: Image 1 Highlights: One-year of radon observations in two stations (SW of Europe) were studied. Urban and rural stations located at opposing sides of a phosphogypsum repository. Atmospheric stagnant conditions favored high radon at the urban station. Rural site required atmospheric stagnation and radon transport from the repository. The repository modulates radon concentrations in this region.